Technological advances in radiotherapy for esophageal cancer - Vosmik, Milan; Petera, Jiri; Sirak, Igor; Hodek, Miroslav; Paluska, Petr; Dolezal, Jiri; Kopacova, Marcela (World journal of gastroenterology, 2010)
Radiotherapy with concurrent chemotherapy and surgery represent the main treatment modalities in esophageal cancer. The goal of modern radiotherapy approaches, based on recent technological advances, is to minimize post-treatment complications by improving the gross tumor volume definition (positron emission tomography-based planning), reducing interfraction motion (image-guided radiotherapy) and intrafraction motion (respiratory-gated radiotherapy), and by better dose delivery to the precisely defined planning target volume (intensity-modulated radiotherapy and proton therapy). Reduction of radiotherapy-related toxicity is fundamental to the improvement of clinical results in esophageal cancer, although the dose escalation concept is controversial.
Keywords: dávka záření; adjuvantní radioterapie; radiační poranění; výsledek terapie; radioterapie počítačová; Radiation Injuries; Esophagectomy; Radiotherapy, Computer-Assisted; Humans; Radiation Dosage; ezofagektomie; Esophageal Neoplasms; plánování radioterapie pomocí počítače; adjuvantní chemoterapie; Radiotherapy, Adjuvant; Chemotherapy, Adjuvant; Treatment Outcome; nádory jícnu; lidé; Radiotherapy Planning, Computer-Assisted